THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, MOTIVATION, AND COMMITMENT ON EMPLOYEE PERFORMANCE AT PT JASA ANGKASA SEMESTA TBK, MEDAN - Sariani; Surya Bakti (International Journal Management and Economic, 2026)
This study examines the effect of transformational leadership, work motivation, and organizational commitment on employee performance at PT Jasa Angkasa Semesta Tbk, Medan. Using a quantitative explanatory approach, data were collected from 60 employees through a structured questionnaire and analyzed using multiple linear regression with SPSS. The results indicate that transformational leadership, motivation, and organizational commitment each have a positive and significant effect on employee performance. Partial testing shows that commitment is the most dominant factor influencing performance, followed by transformational leadership and motivation. Simultaneously, the three independent variables significantly explain employee performance, with a coefficient of determination of 73 percent. These findings highlight the importance of effective leadership practices, motivational strategies, and commitment-building efforts in enhancing employee performance, particularly in aviation support service organizations characterized by high operational demands. This study contributes to human resource management literature and provides practical implications for managers in improving organizational performance through strategic people management